Genotypic difference in green stem disorder severity and vegetative storage protein accumulation affected by different degrees of sink limitation in soybeans [Glycine max (L.) merr.] - Jiuning Zhang; Tatsuhiko Shiraiwa; Tomoyuki Katsube-Tanaka (Plant Production Science)
Green stem disorder (GSD) delays leaf and stem senescence even after pods mature in soybean. In this study, the relationship between GSD severity and vegetative storage protein (VSP) dynamics was investigated under different timings and intensities of depodding treatments. Short growth period (Yukihomare, Yu), GSD-susceptible (Tachinagaha, Tc), and GSD-resistant (Touhoku 129, Th) cultivars were grown under repeated depodding treatments from the R3 growth stage by half [R3 (1/2)] or by one-third [R3 (1/3)], under a single-time depodding treatment at the R5 growth stage by half [R5 (single)], and under no depodding (control). Depodding from R3 decreased the pod number and induced GSD for both Yu and Th. However, the pod weight and stem weight per plant were statistically unchanged from those in control, indicating that remaining pods partially served as a surplus source reservoir in Yu and Th. Tc reduced the pod number and pod weight and unchanged the stem weight in depodding treatments from R3 but induced GSD regardless of the treatments. The growth of single-time depodding at R5 was not different from that of control except the growth parameters of Yu. The relative VSP content temporarily increased 14 days after R3 (DAR3) in all the treatments and cultivars. Although the relative VSP content decreased afterward in Yu and Th, that of Tc increased according to the depodding intensity. In the depodding experiments over three years, a negative correlation tended to be found after 28 DAR3 between VSP accumulation and GSD severity in Th but not in Tc, suggesting that the mechanism underlying N metabolism and GSD occurrence was different between cultivars.